ANALISIS MEDIA PEMBELAJARAN PADA BUKU TEKS IPS MATERI SEJARAH KELAS VII KURIKULUM 2013 - Arifin Suryo Nugroho; Sumiyatun Septianingsih (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2014)
This study aims to uncover the history of the subject matter contained in the curriculum social studies textbooks in 2013, the dominant type of media that the material on the history of class VII social studies textbook curriculum 2013 and the suitability of the material history of instructional media are implemented in social studies textbook curriculum 2013. The method used is descriptive qualitative analysis of exactly which studies document. The results of this study indicate historical material Class VII social studies curriculum in 2013 that is dispersed in the Subject “Social Life in the Future Praaksara Indonesian Society, Hindu-Buddhist and Isla”, “The Factors that Influence Social and Cultural Diversity” , and “contacts with the state another”. In Class VII social studies book historical material, the dominance of media images are quite striking, reaching 90 % , the rest is history map media. Textbook curriculum developed in 2013, when viewed from a number of emerging media support has been quite a lot of text. This is certainly related to the philosophy of the curriculum in 2013 where learning begins from the concrete toward abstract, so that the role of the media in the learning process and the learning support facilities such as text books is very important to realize. Despite of media analysis in textbooks, media availability is quite good, but the creativity of the teacher in a more varied use of media is necessary. Keywords : learning media, social studies textbooks, historical materials, curriculum 2013